Pemanfaatan Media Sosial sebagai Sarana Edukasi Politik bagi Mahasiswa FKIP Universitas Tanjungpura - Alya, Rabiatul; Ilhami, Miftah Jamil; Ananda, Dhea; Hafizi, M Zainul (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze how students of the Faculty of Teacher Training and Education (FKIP) at Universitas Tanjungpura utilize social media as a means of political education, and to identify supporting factors and challenges. This phenomenon is significant because social media now serves as a new public space influencing the mindset, critical attitudes, and political awareness of the younger generation. Using a qualitative descriptive method, data were collected through in-depth interviews, direct observations, and relevant document analysis involving 16 active social media users. The findings indicate that social media platforms such as Instagram, TikTok, and WhatsApp play an important role in enhancing students’ understanding of civic rights and duties, broadening access to political information, and encouraging participation in public discourse. However, challenges identified include the spread of hoaxes, political fatigue, and limited digital literacy. Theoretically, this study contributes to the understanding of digital political socialization by highlighting social media's dual function as an educational platform and a space vulnerable to misinformation. Practically, it underscores the need for sustained digital literacy enhancement and academic support to effectively leverage social media for nonformal political education. This study emphasizes the importance of synergy between educational institutions and digital spaces in fostering a critical and democratic political culture among students.